Pelatihan Strategi Digital Marketing untuk Meningkatkan Penjualan UMKM di Desa Mojorejo - Nuraeni, Eny; Sunaryo, Agus; Hastuti, Poppy Meilina Dian; Sholeh, Rachmad (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service activity aims to increase the capacity of MSMEs in utilizing digital marketing to expand the market and increase income. The methods used include interactive training, mentoring, and evaluation based on surveys and case studies. The activity was implemented on November 18 - December 23, 2024. The results showed an increase in understanding of digital marketing, the use of social media as a promotional tool, and an increase in participant turnover. However, obstacles such as limited access to technology and inconsistent strategies still require ongoing mentoring. The main recommendation is integration with local stakeholders to build a digital ecosystem that supports MSMEs sustainably